Islamizing Environmental Law in Indonesia; Rethinking the Green Fatwa - Najemi, Andi; Rapik, Mohamad (Faculty of Law, Jambi University, 2024)
The enforcement of environmental law in Indonesia is inseparable from the existence of laws regulating the environment. However, the said law and its enforcement fail on a large scale to ask people to participate positively in environmental protection and conservation. The failure to apply and enforce the law has inspired many activisms to look at Islamic principles as the potential value to help the protection of the environment. In Indonesia, green fatwas have also been enacted to help address the issues. While many articles and academic works begin to propose Islamic environmentalism, this article goes even further by proposing the Islamization of environmental legislation. As a doctrinal study, this article relies on legal material related to the topic of green fatwas and environmental law. To sharpen the analysis, this article also employs social engineering theory. This article demonstrates dualism between the green fatwas and environmental law has resulted in the failure to attract people’s compliance. Therefore, the article recommends that assimilation between the green fatwas and the environmental law be made in the future politics of law concerning environmental law.